FRI0434 Blood Hydroxychloroquine (HCQ) Levels do not PREDICT Quality of Life in Systemic Lupus Erythematosus (SLE). (10th June 2014) - Jolly, M.; Galicier, L.; Aumaître, O.; Francès, C.; Le Guern, V.; Lioté, F.; Smail, A.; Limal, N.; Perard, L.; Desmurs-Clavel, H.; Boutin, D.; Asli, B.; et al.
Abstract : Background: Benefits of use of HCQ on physician reported outcomes (PRO) have been well documented in SLE and Rheumatoid arthritis (RA). HCQ can be measured in blood ([HCQ]) and a target threshold of 1000ng/ml has been proposed. No studies have assessed the predictive role of [HCQ] on PRO in SLE. Objectives: Assess the predictive value of [HCQ] with health related quality of life (HRQOL) among patients with SLE. Methods: Data from the PLUS study (a prospective randomized, double-blind, placebo-controlled, multicentre study comparing standard and adjusted HCQ dosing schedules and [HCQ]) were utilized. Blood HCQ levels were quantified by HPLC, along with HRQOL PRO assessments (Medical Outcomes Study-Short Form 36 or SF-36) at baseline (J0) and month 7 visits (M7). Paired t test were used to compare HCQ concentrations at the two visits. Spearman correlation coefficients between HCQ concentrations (continuous variable) and HRQOL at J0 and M7 were obtained. Nonparametric t test to compare HRQOL (J0) stratified by HCQ concentrations categories (0-499, 500-1000, >1000 ng/ml) was performed. Linear regression analysis with physical or mental component summary scores as dependent variables, and HCQ (J0) concentration as the predictor variable was performed. P value of ≤0.05 on two tailed tests was considered significant. Results: 166 SLE patients' data were analyzed. Mean (SD) age and disease duration were 44.4 (10.7) and 9.3 (6.8) years. Eighty seven percent were women. Mean (SD, median, IQR) HCQ concentrations in the blood at J0 were 660 (314, 615, 424) ng/ml and increased to 1020 (632, 906, 781) ng/ml at M7 (mean difference 366 units, 95% CI -472 to -260, p<0.001), and there was a weak correlation between the two readings (r 0.21, p=0.009). No significant correlations between HCQ concentrations with SF-36 HRQOL domains at J0 or M7 were noted. There were no differences in HRQOL stratified by HCQ concentrations. HCQ concentrations at J0 or changes in HCQ concentration (M7-J0) were not predictive of HRQOL at M7 or changes in HRQOL (M7-J0). No significant changes in HRQOL were present at J0 and M7. Conclusions: No association of HCQ concentrations with current or future HRQOL (when measured by SF36) were found. This could be a real finding, or reflect inadequacy of sample size or the tool used to capture relevant HRQOL in SLE. Latter is hypothesized as no changes in HRQOL over time were noted irrespective of HCQ concentrations, despite physician-assessed changes in disease activity. Further studies are suggested. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2311